The Deprofessionalisation Thesis, Accountability and Professional Character - Chris Clark (Social Work & Society, 2005)
It is said that the deprofessionalisation of social work and other welfare occupations reduces workers' professional discretion and autonomy, and thus their capacity to act in the best interests of their client. Without necessarily regarding the deprofessionalisation thesis as conclusive, this paper will ask how the state's control of the role and task of social workers impacts on their role-implicated obligations as professionals. If workers are reduced (as claimed) to the status of mere functionaries in systems they neither approve of nor control, does this exonerate them from bad outcomes or service failures? How should we view the dramatic increase in formal regulation now seen in the UK - as professionalisation or deprofessionalisation? The paper will argue that whatever the drift of policy, workers remain in some measure personally accountable. Service failures imply faults of practical reason that are partly attributable to the moral and intellectual character of professionals as individuals. It is therefore up to professionals, and their organisations, to attend to the improvement of professional character.